Education and Consent for Population-Based DNA Screening: A Mixed-Methods Evaluation of the Early Check Newborn Screening Pilot Study - Peay, Holly L.; Gwaltney, Angela You; Moultrie, Rebecca; Cope, Heidi; Boyea, Beth Lincoln‐; Porter, Katherine Ackerman; Duparc, Martin; Alexander, Amir A.; Biesecker, Barbara B.; Isiaq, Aminah; Check, Jennifer; Gehtland, Lisa; et al. (Frontiers in Genetics, 2022)
A challenge in implementing population-based DNA screening is providing sufficient information that is understandable and acceptable, and that supports informed decision making. Early Check is an expanded newborn screening study offered to mothers/guardians whose infants have standard newborn screening in North Carolina. We developed electronic education and consent to meet the objectives of feasibility, acceptability, trustworthiness, and supporting informed decisions. We used two methods to evaluate Early Check among mothers of participating infants who received normal results: an online survey and interviews conducted via telephone. Survey and interview domains included motivations for enrollment, acceptability of materials and processes, attitudes toward screening, knowledge recall, and trust. Quantitative analyses included descriptive statistics and assessment of factors associated with knowledge recall and trust. Qualitative data were coded, and an inductive approach was used to identify themes across interviews. Survey respondents (n=1,823) rated the following as the most important reasons for enrolling their infants: finding out if the baby has the conditions screened (43.0%), and that no additional blood samples were required (20.1%). Interview respondents (n=24) reported the value of early knowledge, early intervention, and ease of participation as motivators. Survey respondents rated the study information as having high utility for decision making (mean 4.7 to 4.8 out of 5) and 98.2% agreed that they had sufficient information. Knowledge recall was relatively high (71.8% to 92.5% correct), as was trust in Early Check information (96.2% strongly agree/agree). Attitudes about Early Check screening were positive (mean 0.1 to 0.6 on a scale of 0-4, with lower scores indicating more positive attitudes) and participants did not regret participation (e.g., 98.6% strongly agreed/agreed Early Check was the right decision). Interview respondents further reported positive attitudes about Early Check materials and processes. Early Check provides a model for education and consent in large-scale DNA screening. We found evidence of high acceptability, trustworthiness and knowledge recall, and positive attitudes among respondents. Population-targeted programs need to uphold practices that result in accessible information for those from diverse backgrounds. Additional research on those who do not select screening, although ethically and practically challenging, is important to inform population-based DNA screening practices.